TO THE QUESTION OF CIVILIZATIONAL DEVELOPMENT OF SOCIETY - Dosmurzaevich, Azamat Baymurzaev (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the question of civilizational development of society. On this way, research papers needs to make analyses of the society. Finally, research has concluded with the major research analyses from different points of the view.